EFEKTIVITAS MODEL PEMBELAJARAN SELF DIRECTED LEARNING (SDL) SETTING KOOPERATIF TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIKA SISWA SMA NEGERI 5 PADANGSIDIMPUAN - Sinta, Feni Raz; Lubis, Roslian; Ahmad, Marzuki (JURNAL MathEdu (Mathematic Education Journal), 2024)
Abstrak This research aims to determine the effectiveness of the Self Directed Learning (SDL) Cooperative Setting learning model on the mathematical critical thinking abilities of students at SMA Negeri 5 Padangsidimpuan. This research uses an experimental method with a One group pretest-posttest design. The research population was the entire class XI students of SMA Negeri 5 Padangsidimpuan, totaling 177 people. The research sample used cluster random sampling techniques, namely class XI MIA 3 with a total of 27 people. The research instruments were tests of critical thinking skills in mathematics and observation sheets of learning activities. The data analysis used is descriptive analysis and inferential statistics using the paired t-test. Based on descriptive analysis, it can be found (1) the average of using the Self-Directed Learning (SDL) Cooperative Setting learning model is 3.54 (very good category) and (2) the average of students' mathematical critical thinking abilities before using the learning model Self-Directed Learning (SDL) Cooperative Setting is 51.81 and after using the Self-Directed Learning (SDL) learning model Cooperative Setting is 85.56. Furthermore, based on inferential statistics using paired samples test, (SPSS version 26), the results show significant value is less than 0.05 (0.000 < 0.05). This means that there is effectiveness in using the Self-Directed Learning (SDL) Cooperative Setting learning model on students' mathematical critical thinking abilities in class XI MIA 3 SMA Negeri 5 Padangsidimpuan. Keywords: Self Directed Learning Model, Cooperative Setting, Critical Thinking Skills